Toco, North Trinidad - (:unkn) unknown (Pereira and Co. Ltd., Trinidad, 2009)
Coastal view of the north-east coast of Trinidad near Toco
Black and White; Landscape
Keywords: Postcards; Trinidad and Tobago; Coastal scenery; Cities and towns--Toco